Relationship between knowledge level and contraceptive compliance among family planning acceptors: A Cross-Sectional Study - Suprapto Suprapto (Journal Interdisciplinary Health, 2026)
Introduction: Contraceptive compliance is a key determinant of the effectiveness of family planning programs. Inadequate compliance may lead to contraceptive failure, unintended pregnancy, and reduced confidence in family planning services. Knowledge level is considered an important factor influencing compliance; however, empirical evidence linking knowledge to contraceptive compliance remains limited, particularly in primary health care settings. This study aimed to examine the relationship between knowledge level and contraceptive compliance among family planning acceptors. Methods: A quantitative analytical study with a cross-sectional design was conducted at selected primary health care facilities. The study involved 50 women of reproductive age who were active family planning acceptors. Data were collected using a structured questionnaire assessing socio-demographic characteristics, knowledge of contraception, and contraceptive compliance. Knowledge levels were categorised as low, moderate, or high, while the correct and consistent use of contraceptive methods and adherence to follow-up schedules were used to assess compliance. Data analysis included descriptive statistics and chi-square tests, with a significance level set at p < 0.05. Results: 44.0% of respondents had a high level of knowledge, 36.0% had moderate knowledge, and 20.0% had low knowledge. Overall, 62.0% of respondents were compliant with contraceptive use. A statistically significant relationship was found between knowledge level and contraceptive compliance (p = 0.012). Respondents with high knowledge levels demonstrated the highest compliance rate (81.8%), while non-compliance was most prevalent among those with low knowledge levels (70.0%). Conclusion: Knowledge level is significantly associated with contraceptive compliance among family planning acceptors. Strengthening structured and client-centred educational and counselling interventions is essential to improve contraceptive compliance and enhance the effectiveness of family planning programs